Impacts of Microbial Activity on the Optical and Copper-Binding Properties of Leaf-Litter Leachate - Cuss, Chad; Gueguen, Celine (Frontiers in Microbiology, 2012)
Dissolved organic matter (DOM) is a universal part of all aquatic systems that largely originates with the decay of plant and animal tissue. Its polyelectrolytic and heterogeneous characters make it an effective metal-complexing agent with highly diverse characteristics. Microbes utilize DOM as a source of nutrients and energy and their enzymatic activity may change its composition, thereby altering the bioavailability and toxicity of metals. This study investigated the impacts of microbial inoculation upon the optical and copper-binding properties of freshly produced leaf-litter leachate over 168 h. Copper speciation was measured using voltammetry, and using fluorescence quenching analysis of independent fluorophores determined using parallel factor analysis (PARAFAC). Two protein/polyphenol-like and two fulvic/humic-like components were detected. Thirty-five percent of total protein/polyphenol-like fluorescence was removed after 168-h of exposure to riverine microbes. The microbial humic-like and tryptophan-like PARAFAC components retained significantly different log K values after 168 h of incubation (p < 0.05), while their complexing capacities were similar. Using voltammetry, a sixfold increase in copper-complexing capacity (CC, from 130 to 770 μmol Cu g C−1) was observed over the exposure period, while the conditional binding constant (log K) decreased from 7.2 to 5.8. Overall binding parameters determined using voltammetry and fluorescence quenching were in agreement. However, the electrochemically based binding strength was significantly greater than that exhibited by any of the PARAFAC components, which may be due to the impact of non-fluorescent DOM, or differences in the concentration ranges of metals analyzed (i.e., different analytical windows). It was concluded that the microbial metabolization of maple leaf leachate has a significant impact upon DOM composition and its copper-binding characteristics.